Role of hydroxypropyl-β-cyclodextrin on freeze-dried and gamma-irradiated PLGA and PLGA–PEG diblock copolymer nanospheres for ophthalmic flurbiprofen delivery - Vega E (Dove Medical Press, 2012)
Estefanía Vega1, M Antònia Egea1, Ana Cristina Calpena2, Marta Espina1, M Luisa García11Department of Physical Chemistry, 2Department of Biopharmacy and Pharmaceutical Technology, Institute of Nanoscience and Nanotechnology, Faculty of Pharmacy, University of Barcelona, Barcelona, SpainAbstract: Poly(D,L-lactide-co-glycolide) and poly(D,L-lactide-co-glycolide) with poly(ethylene glycol) nanospheres (NSs) incorporating flurbiprofen (FB) were freeze-dried with several cryoprotective agents and sterilized by γ-irradiation. Only when 5.0% (w/v) hydroxypropyl-β-cyclodextrin (HPβCD) was used, a complete resuspension by manual shaking and almost identical particle size of the NSs was obtained after freeze-drying. In vitro drug release and ex vivo corneal permeation of NSs with and without HPβCD were evaluated. The presence of HPβCD resulted in a reduction of burst effect, providing a more sustained release of the drug. A significant decrease in the FB transcorneal permeation of NSs containing HPβCD was obtained, related to the slower diffusion of FB observed in the in vitro results. The uptake mechanism of the NSs was examined by confocal microscopy, suggesting that NSs penetrate corneal epithelium through a transcellular pathway. Ocular tolerance was assessed in vitro and in vivo by the Eytex™ and Draize test, respectively. Long-term stability studies revealed that γ-irradiated NSs stored as freeze-dried powders maintained their initial characteristics. Stability studies of the resuspended NSs after 3 months of storage in the aqueous form showed that NSs were stable at 4°C, while formulations stored at 25°C and 40°C increased their initial particle size.Keywords: nanospheres, poly(D,L-lactide-co-glycolide), poly(ethylene glycol), hydroxypropyl-β-cyclodextrin, freeze-drying, γ-irradiation